Comparison of Extraction Solvents and Techniques Used for The Assay of Free and Bound Phenolic Acids from Rice Samples - Seesom, Chaweewan; Jumepaeng, Thanawat; Luthriac, Devanand L.; Chanthai, Saksit (Journal of Food Health and Bioenvironmental Science, 2018)
The extraction and alkaline hydrolysis methods of free and bound phenolic acids were studied on Jasmine (Jasmine 85), Basmati (Basmati 370-1) and brown rice (Jasmine 85) (Oryza satia L.). Free phenolic acids in three rice samples were extracted by seven different solvent systems: 100% and 80% (v/v) methanol, 100 % and 80% (v/v) ethanol, 100% (v/v) water, 80% (v/v) acetone, and 35:35:30 % (v/v/v) of methanol:acetone:water with five different extraction techniques (shaker, regular ultrasonic (RUAE), high energy ultrasonic (HUAE), microwave (MAE) and pressurized liquid extraction (PLE)). The phenolic extracted contents were analyzed by the ferric reducing antioxidant power (FRAP) assay. Moreover, three different alkaline hydrolysis techniques: ultrasonic (UAAH), microwave (MAAH), and pressurized liquid assisted alkaline hydrolysis extraction (PAAH) were used for extracting bound phenolic acids and analyzed by liquid chromatography-mass spectrometry. Maximum extraction yields of total phenolic acids were obtained from 35:35:30 % (v/v/v) of methanol/acetone/water as solvent system with PLE technique while bound phenolic acids were obtained by MAAH technique. In addition, MAAH technique provides the highest extraction yields of bound phenolic acids. PLE and MAAH techniques were suitable for free and bound phenolic acids extraction from rice samples, respectively.